Development of Plate Reader and On-Line Microfluidic Screening to Identify Ligands of the 5-Hydroxytryptamine Binding Protein in Venoms - Otvos, Reka A. (Toxins (Basel), 2015)
The 5-HT(3) receptor is a ligand-gated ion channel, which is expressed in the nervous system. Its antagonists are used clinically for treatment of postoperative- and radiotherapy-induced emesis and irritable bowel syndrome. In order to better understand the structure and function of the 5-HT(3) receptor, and to allow for compound screening at this receptor, recently a serotonin binding protein (5HTBP) was engineered with the Acetylcholine Binding Protein as template. In this study, a fluorescence enhancement assay for 5HTBP ligands was developed in plate-reader format and subsequently used in an on-line microfluidic format. Both assay types were validated using an existing radioligand binding assay. The on-line microfluidic assay was coupled to HPLC via a post-column split which allowed parallel coupling to a mass spectrometer to collect MS data. This high-resolution screening (HRS) system is well suitable for compound mixture analysis. As a proof of principle, the venoms of Dendroapsis polylepis, Pseudonaja affinis and Pseudonaja inframacula snakes were screened and the accurate masses of the found bioactives were established. To demonstrate the subsequent workflow towards structural identification of bioactive proteins and peptides, the partial amino acid sequence of one of the bioactives from the Pseudonaja affinis venom was determined using a bottom-up proteomics approach.